Identification and provenance analysis of sediments’ end-members in the typical black soil area of northeast China - Chen, Peng; Qi, Jiahao; Ma, Junchi; Jing, Yuan; Sun, Hao; Wang, Chunpeng; Huang, Jiangyin (Frontiers in Earth Science, 2026)
IntroductionThe Songnen Plain is a significant black soil region in China, where the sedimentary processes and provenance of sediments are crucial for reconstructing the regional environmental evolution.MethodsIn this study, end-member modeling analysis coupled with geochemical proxies of major and trace elements was applied to systematically investigate the grain-size distribution and sediment sources in the northwestern margin of the Songnen Plain. Paired samples from surface (0.2 m) and subsurface (1.0 m) layers across different geomorphic units were compared.ResultsFour to six distinct grain-size end members were identified, with their number and characteristics varying across geomorphic units.DiscussionThese include long-range aeolian dust (EM1), mid-range suspended aeolian material (EM2), mid-to short-range wind-sorted sand (EM3), fluvial suspended and channel deposits (EM4-5), and slope mud-flow deposits (EM6). Aeolian end-members (EM1-3) dominate both surface and subsurface sediments (>71%), whereas fluvial components (<29%) were mainly derived from the Greater Hinggan Mountains and local sources. Provenance analysis further indicates that the Horqin Sandy Land, rather than the Songnen Sandy Land, served as the primary aeolian source. This study provides new sedimentological evidence for understanding the provenance and depositional mechanisms on the northwestern margin of the Songnen Plain.